قياس أثر التغيرات في سعر الفائدة على حجم الودائع و القروض في البنوك التجارية الأردنية ( دراسة حالة بنك القاهرة – عمان ) . - النويران, طارق (جامعة الوادي- University of Eloued, 2017)
It emerged as a problem in the study to identify the extent of bank deposits in response to the various changes in interest rates? As well as to identify the extent of bank loans and advances to changes in bank deposits in response? The study aims to determine the impact of changing interest rates on decisions related to the size of bank deposits prices. And find out the impact of changes in the volume of bank deposits on bank loans. To achieve this, the researcher applied on Bank Cairo - Amman, and collect the necessary data for the period 2011-2015 m from the annual reports of the bank. The researcher in the study of descriptive and analytical approach to answer the questions the study, its hypotheses. The study concluded that the results of a group including: the existence of a statistically significant positive relationship between the variable interest rate and the size of the deposits and the size of savings deposits. While the study did not monitor the strong relationship between the weighted average interest rate and current deposits, as well as the results indicated the presence of a statistically significant positive relationship between the size of bank deposits, the different, the volume of bank loans. The researcher presented the study at the end of a set of recommendations that would contribute to the success of the commercial banking business, and activate their role in the revitalization of the national economy, and pay haste towards the growth and development through the efficient management of its assets and liabilities
Measuring the effect of changes in interest rates on deposits and loans in the Jordanian commercial banks price (Case study Bank of Cairo - Amman)
مقال
Keywords: bank. interest .growth and development